PENGARUH PENDEKATAN DEEP LEARNING DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN CRITICAL THINKING SISWA SMK PALEBON - Syifa Urosidah; Arif Wahyu Wirawan (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Critical thinking skills are one of the essential competencies that vocational education students must possess to face the challenges of the workforce. However, these skills have not yet developed optimally, necessitating learning strategies that can foster deep understanding and enhance students’ motivation to learn. This study aims to analyze the influence of the deep learning approach and learning motivation on the critical thinking skills of 11th-grade MPLB students at SMK Palebon in Semarang. The study employed a quantitative approach with an associative research design. The study population consisted of 50 students, all of whom were included in the sample using saturation sampling. Data were collected via a questionnaire, and data analysis was conducted using multiple linear regression with SPSS version 26. The research findings indicate that the deep learning approach and learning motivation significantly influence critical thinking skills. These results offer practical implications for teachers and schools to optimize the implementation of the deep learning approach—supported by strategies to enhance learning motivation—as a means to develop students' critical thinking skills in vocational education. As the study was limited to a single school with a relatively small number of respondents, the findings cannot be broadly generalized. The results of this study provide practical implications for teachers and schools to optimize the implementation of a deep learning approach supported by strategies to enhance learning motivation as an effort to develop students’ critical thinking skills in vocational education. This study was limited to a single school with a relatively small number of respondents; therefore, the results cannot yet be widely generalized.